Quasi-static indentation response of pedestrian bridge multicellular pultruded GFRP deck panels. (15th August 2016) - Sutherland, L.S.; Sá, M.F.; Correia, J.R.; Guedes Soares, C.; Gomes, A.; Silvestre, N.
Highlights: Specimen geometry must be carefully selected to ensure correct simulation of full scale behaviour. Indenter size and shape influenced results, both qualitatively and quantitatively. A surface coating successfully delayed the first significant damage. Surface coating and foam filling protections did not improve perforation resistance. Unprotected surface susceptible to damage due to heavier pedestrians in high-heels. Abstract: This paper presents an experimental study of the quasi -static indentation behaviour of a pultruded glass fibre reinforced polymer (GFRP) multicellular deck panel used in footbridges. To simulate the applied loads to be experienced by such a deck during its service life, various sets of specimens extracted from the panel cross-section were perforated statically across its top flange thickness using different indenters. Load-displacement responses, failure modes and absorbed energies were analysed concerning the influence of the following parameters: (i) specimen geometry (single laminated flange, 1-cell and 3-cells); (ii) indenter type (size – 6/10 mm and shape – hemispherical/flat), and (iii) damage protection (surface coating and filling of the section cavities with polyurethane foam). The results obtained show that simpler specimen geometries are able to predict the quasi-static indentation behaviour of the bridge deck in particular cases and for specific measured responses; nonetheless, they are not able to simulate the effects of damage protections. The application of a surface coating proved to be the only successful protection method in delaying the first significant damage, giving higher absorbed energy levels. However, regarding the onset of perforation, both protection strategies considered did not provide any appreciable improvement. The results obtained also show that penetration failure modes due to "standard" high-heel loads are not likely to occur on the bridge deck even if its surface is not protected. Nevertheless, in this case, both initial damage and perforation may be easily inflicted by heavier pedestrians walking or running upon "stiletto-type" high-heels.